TDA/H: uma leitura possível - Lima, Michelle Calheiros (2016)
The psychiatry classifies the aspects of psychopathology by the Diagnostic and Statistical Manual of Mental Disorders. This Manual, throughout its history, passes through many changes and variety versions. The object of this research is making a critical analysis about the ADHD diagnosis, as described by the psychiatry taking as reference the psychoanalysis. The choice of psychoanalysis as guiding element of this critical reading is due to the importance of consider the unique history and the singularity as inherent to the subject, while seek to listen and offer the word for each one. This paper have these specific purposes: discuss how the signs and symptoms evidence helped on the reflection about the ADHD diagnosis; demonstrate the psychoanalytical understanding of the subjective dimension and the psychic apparatus; present the parallelism among the modifications on social and production of new subjective symptoms. To achieve this proposal we have opted to use the DSM-V, in the most recent edition, as well as Manual para Diagnóstico e Tratamento do Transtorno de Deficit de Atenção/Hiperatividade TDA/H , third edition. However, consider the social in its consumer ideology, crossed by modifications at the symbolic law is fundamental for the research, after all, the postulates of post-modernity ignore the subjectivity, exalt all kinds of excess, contributing to erase the limits. The questioning about ADHD diagnosis mode is justified because it is served by merely statistical methodology and the lack of an etiology for referred disorder. As well as, the disregard of the subject singularity and his submission to unconscious processes that seeks satisfaction, because the mental organization and pulsional economy are individual and unique. It is know that the organizer potential of certain pulsional resignation, of joy restriction that impose sacrifice and creates unease, however it is fundamental and structuring for the subject. This is a research with theoretical character, that use as method the critical analysis of ADHD, according to presented in DSM-V, under viewpoint of psychoanalysis. It seeks to offer other achievable reading to think the ADHD.